Hypogonadotropic Hypogonadism due to a Novel Missense Mutation in the First Extracellular Loop of the Neurokinin B Receptor - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (ENDOCRINE SOC, 2009)
Context: The neurokinin B (NKB) receptor, encoded by TACR3, is widely expressed within the central nervous system, including hypothalamic nuclei involved in regulating GnRH release. We have recently reported two mutations in transmembrane segments of the receptor and a missense mutation in NKB in patients with normosmic isolated hypogonadotropic hypogonadism (nIHH). Patients and Methods: Wesequenced the TACR3 gene in a family in which three siblings had nIHH. The novel mutant receptor thus identified was studied in a heterologous expression system using calcium flux as the functional readout. Results: All affected siblingswerehomozygousfor the His148Leu mutation, in the first extracellular loop of theNKBreceptor. The His148Leu mutant receptor exhibited profoundly impaired signaling in response to NKB (EC50 = 3 +/- 0.1 nM and > 5 mu M for wild-type and His148Leu, respectively). The location of the mutation in an extracellular part of the receptor led us also to test whether senktide, a syntheticNKBanalog, mayretain ability to stimulate the mutant receptor. However, the signaling activity of the His148Leu receptor in response to senktide was also severely impaired (EC50 = 1 +/- 1 nM for wild-type and no significant response of His148Leu to 10 mu M). Conclusions: Homozygosity for the TACR3 His148Leu mutation leads to failure of sexual maturation in humans, whereas signaling by the mutant receptor in vitro in response to either NKB or senktide is severely impaired. These observations further strengthen the link between NKB, the NKB receptor, and regulation of human reproductive function. (J Clin Endocrinol Metab 94: 3633 -3639, 2009)
Keywords: FOLLICLE-STIMULATING-HORMONE; GONADOTROPIN-SECRETION; LUTEINIZING-HORMONE; HUMAN HYPOTHALAMUS; RAT HYPOTHALAMUS; SUBSTANCE-P; GPR54; DOMAINS; PUBERTY; GENE